Concomitant Treatment with Etanercept and Tacrolimus Synergistically Attenuates Arthritis Progression via Inhibition of Matrix Metalloproteinase-3 Production and Osteoclastogenesis in Human TNF-α Transgenic Mice - Iwao Seki; Miwa Takai-Imamura; Tomomi Kohara-Tanaka; Satoshi Shirae; Minoru Sasano; Hiroaki Matsuno; Hiroyuki Aono (Mediators of Inflammation)
In the present study, we investigated the effects and mechanisms of action of a combined treatment with etanercept, a soluble tumor necrosis factor receptor (p75) Fc fusion protein, and tacrolimus, a calcineurin inhibitor on the progression of arthritis in human tumor necrosis factor-α (TNF-α) transgenic (hTNF-Tg) mice. Single-drug treatments with etanercept and tacrolimus attenuated the clinical signs but not the radiographic changes associated with the development of arthritis in mice. On the contrary, combined treatment significantly suppressed the radiographic progression and also improved the clinical signs. The combined treatment exhibited synergistic effects of the two drugs in reducing the serum matrix metalloproteinase-3 level and the number of peripheral CD11bhigh osteoclast precursor cells. Moreover, tacrolimus inhibited the cytokine-induced osteoclast differentiation in synergy with etanercept in an in vitro assay. Interestingly, tacrolimus did not inhibit the production of antidrug antibodies (ADAs) against etanercept in the hTNF-Tg mice. This result implies that the synergistic effects of etanercept and tacrolimus are not due to secondary effects derived from the suppression of ADA production by tacrolimus but are due to their primary effects. These findings suggest that concomitant treatment with etanercept and tacrolimus may be one of preferable treatment options to control disease activities for patients with rheumatoid arthritis, especially for those with bone resorption.